Eclecticism in the Compilation of Islamic Law in Book 1 - M. Nasrul Arifin; Mujamil Qomar; Ahmad Muhtadi Anshor (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Eclecticism in the Compilation of Islamic Law (KHI) is evident through the incorporation of various opinions from different schools of Islamic jurisprudence, including the Shafi‘i school as the dominant madhhab in Indonesia, as well as the Hanafi, Maliki, and Hanbali schools, alongside several modern approaches. This method reflects an effort to reconstruct Islamic law so that it aligns with social needs and the national legal system. This study employs a library research method. The primary sources consist of the official text of the KHI, classical fiqh works from the four major schools (Hanafi, Maliki, Shafi‘i, and Hanbali), and contemporary literature on Islamic family law in Indonesia. The analytical techniques used include document study, article content analysis, and tracing the compatibility of madhhab opinions with the norms adopted in the KHI, supplemented by a sociological approach to assess the implications of its implementation in practice. The findings indicate that the application of eclecticism in Book I of the KHI is grounded in (a) social plurality; (b) the sustainability of the national legal system; (c) the values of justice; and (d) legal adaptability. The procedural steps of madhhab-based eclecticism in the KHI involve: (a) identifying issues of Islamic law to be compiled, (b) examining textual evidences and madhhab opinions, (c) selecting the most beneficial view (maslahah), (d) harmonizing it with the national legal system, and (e) conducting academic validation and social feasibility testing.